(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Survey the situation of antibiotic use in outpatient treatment of otolaryngological diseases at the Department of Ear, Nose and Throat, Vinh Medical University Hospital in 2022. Research method: Retrospective study on outpatient prescriptions at the Ear-Nose-Throat Department of Vinh Medical University Hospital from April 2022 to April 2023. Research results: The five most common ENT diseases in the study sample are pharyngitis (42.39%), rhinitis (23.91%), chronic sinusitis (14.6%), and tonsillitis (12.5%) and otitis media (6.53%). The highest rate of ENT diseases occurs in the age group 16-60 years old (65.76%). There are 16 antibiotics used, of which amoxicillin-clavulanate is used the most (40.76%); The lowest are cefaclor, rifamycin and tyrothricin (with a rate of 0.54%). There are five types of antibiotics to treat otitis media - azithromycin (41.67%); There are three types of antibiotics to treat chronic sinusitis - amoxicillin-clavulanate (92.6%); There are five types of antibiotics to treat rhinitis - amoxicillinclavulanate (81.82%); There are 12 types of antibiotics to treat sore throat - sultamicillin is used (25.64%); There are 12 types of antibiotics to treat tonsillitis: amoxicillin- sulbactam is the most used antibiotic (17.37%). Single regimens account for the majority of treatment regimens (80.43%). Conclusion: The most used antibiotics are the beta-lactam group and penicillin antibiotics combined with beta-lactamase inhibitors. Single regimens make up the majority of treatment regimens.